Molecular characterization of an anthocyanin-related glutathione S-transferase gene in Japanese gentian with the CRISPR/Cas9 system - Tasaki, Keisuke (BMC Plant Biol, 2020)
BACKGROUND: The blue pigmentation of Japanese gentian flowers is due to a polyacylated anthocyanin, gentiodelphin, and all associated biosynthesis genes and several regulatory genes have been cloned and characterized. However, the final step involving the accumulation of anthocyanins in petal vacuoles remains unclear. We cloned and analyzed the glutathione S-transferases (GSTs) in Japanese gentian that are known to be involved in anthocyanin transport in other plant species. RESULTS: We cloned GST1, which is expressed in gentian flower petals. Additionally, this gene belongs to the Phi-type GST clade related to anthocyanin biosynthesis. We used the CRISPR/Cas9-mediated genome editing system to generate loss-of-function GST1 alleles. The edited alleles were confirmed by Sanger and next-generation sequencing analyses. The GST1 genome-edited lines exhibited two types of mutant flower phenotypes, severe (almost white) and mild (pale blue). The phenotypes were associated with decreased anthocyanin accumulation in flower petals. In the GST1 genome-edited lines, sugar-induced stress conditions inhibited the accumulation of anthocyanins in stems and leaves, suggestvhing that GST1 is necessary for stress-related anthocyanin accumulation in organs other than flowers. These observations clearly demonstrate that GST1 is the gene responsible for anthocyanin transport in Japanese gentian, and is necessary for the accumulation of gentiodelphin in flowers. CONCLUSIONS: In this study, an anthocyanin-related GST gene in Japanese gentian was functionally characterized. Unlike other biosynthesis genes, the functions of GST genes are difficult to examine in in vitro studies. Thus, the genome-editing strategy described herein may be useful for in vivo investigations of the roles of transport-related genes in gentian plants.